1991
DOI: 10.1021/bi00238a008
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between magainin 2 and Salmonella typhimurium outer membranes: effect of lipopolysaccharide structure

Abstract: The role of the outer membrane and lipopolysaccharide (LPS) in the interaction between the small cationic antimicrobial peptide magainin 2 and the Gram-negative cell envelope was studied by FT-IR spectroscopy. Magainin 2 alters the thermotropic properties of the outer membrane-peptidoglycan complexes from wild-type Salmonella typhimurium and a series of LPS mutants which display differential susceptibility to the bactericidal activity of cationic antibiotics. These results are correlated with the LPS phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 51 publications
(52 reference statements)
7
53
0
Order By: Relevance
“…The extent of peptide disaggregation is less pronounced with LPS containing short sugar side chains. Such a phenomenon might be hindered by a change in the OM fluidity, which has been shown to decrease significantly as the LPS-polysaccharide region reduces its length and becomes less disordered (62,63). This can be interpreted in part to result from the reaction between the divalent cations and the negatively charged groups, mainly the phosphate groups of the disaccharide moiety of lipid A.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of peptide disaggregation is less pronounced with LPS containing short sugar side chains. Such a phenomenon might be hindered by a change in the OM fluidity, which has been shown to decrease significantly as the LPS-polysaccharide region reduces its length and becomes less disordered (62,63). This can be interpreted in part to result from the reaction between the divalent cations and the negatively charged groups, mainly the phosphate groups of the disaccharide moiety of lipid A.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, bacterial membranes are predominantly composed of acidic phospholipids (such as phosphatidylglycerol and cardiolipin) that confer a net negative charge to the surface of the membrane while phosphatidylethanolamine and phosphatidylserine are not detectable [23][24][25]. Since AMPs have to cross the negatively charged lipopolysaccharide layer before reaching the membrane, the possible impact of this barrier has been investigated.…”
Section: Structural Features Of Animal and Bacterial Cellsmentioning
confidence: 99%
“…In these mutants the phosphate groups would, however, be heterogeneous due to further modifications resulting in diverse phosphorylation patterns amongst mutants. It was found that the LPS mutants display differential susceptibility to cationic peptides in a manner that seems to be related to charge location and magnitude and to absence or presence of the O-antigen side chain [23,26]. It is proposed that because of their greater affinity for LPS than divalent cations and their bulkiness, cationic peptides competitively displace these ions and create a passage through the outer bacterial membrane thus propelling themselves to the cytoplasmic membrane by a "self-promoted uptake" [27].…”
Section: Structural Features Of Animal and Bacterial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0-polysaccharide moieties of LPS have been demonstrated to mediate many biological effects, such as resistance to killing by normal, nonspecific serum (43,53,62), resistance to phagocytosis by monocytes, and resistance to killing by cationic peptides (54,64). 0-chain antigens are also important for attachment of bacteriophages and may be * Corresponding author.…”
mentioning
confidence: 99%